An analysis of musharakah agreement due to the bank's negligence in implementing prudential banking principle: The case of jurisprudence at the Supreme Court Cassation Verdict Number 624 K/Ag/2017 - Armaini, Sri; Said, Muhammad (Universitas Islam Indonesia, 2023)
This study analyzed the Supreme Court Cassation Verdict Number 624 K/Ag/2017, regarding the musyarakah agreement between the customer and PT. Bank Sumut Padangsidimpuan Branch, in which the latter had disbursed financing to the customer before the issuance of a life insurance policy letter. The focus of the research was to investigate the settlement of the musharakah agreement due to the negligence of the bank which resulted in the customer’s obligation to pay the remaining debt based on the Supreme Court Cassation Verdict Number 624 K/Ag/2017. The study used a qualitative research approach with a case approach, statute approach, and conceptual approach. This study concludes that based on the Compilation of Sharia Economic Law (Kompilasi Hukum Ekonomi Syariah or KHES) Articles 209-210 if one of the parties in the agreement dies, the contract ends, and the loss caused by the death of the mudharib is borne by the owner of the capital. Therefore, even though in a musyarakah contract there is a mix of assets of both customers and Islamic banks. However, because the bank was negligent in their prudential banking principles practice and this action was against the law, then in regards to the legal protection theory, the losses experienced from the musyarakah contract should have been borne by the bank as a form of punishment for the unlawful act due to negligence in implementing the prudential banking principle.